ANALISIS PENGARUH PERCEIVED QUALITY, PERCEIVED VALUE, DAN PERCEIVED RISK TERHADAP KEPUTUSAN PEMBELIAN ONLINE - Ayu Puspitasari, Dyah; Indriani, Farida (Faculty of Economics and Business Diponegoro University, 2018)
Online shopping sites appear as alternative choices for buyers. Lazada is the most popular online shopping site in Indonesia which has an official website named lazada.co.id. In 2018 Lazada have decrease in the number of visitors which caused a decrease buying interest in Lazada. on the other hand began, many online shops appear that not have official sites and only rely on promotion and sales through social media only. This has an impact on the emergence of alternative purchasing decisions from consumers will buy the product.will buy the product.This research aims to analyze the influence of perceived quality, perceived value, and perceived risk towards the customer’s online purchase decision of official website Lazada and social media online shop EolKPop. The sampling method used on this research is non-probability sampling with purposive sampling technique. Samples were collected from 100 respondents on Semarang who had made an online purchase transaction at official web lazada.co.id and 100 respondents who have made an online purchase transaction in social media online shop Eolkpop. Analysis method used here is multiple regression analysis which includes validity test, reliability test, classic assumption test, multiple linear regression test, t-test, f-test, determination test and independent t test.The result showed that perceived quality and perceived value has positive and significant influence towards the online purchase decision on official website Lazada and social media online shop EolKPop while perceived risk has negative not significant influence towards the online purchase decision on official website Lazada and social media online shop EolKPop.